Macroevolutionary shift in the size of amphibian genomes and the role of life history and climate. Issue 11 (November 2018) - Liedtke, H.; Gower, David; Wilkinson, Mark; Gomez-Mestre, Ivan
Abstract The evolution and great diversity of genome size has been of long-standing interest to biologists, but has seldom been investigated on a broad phylogenetic scale. Here we present a comparative quantitative analysis of factors shaping genome size evolution in amphibians, the extant class of vertebrates with the largest variation in genome size. We find that amphibian genomes have undergone saltations in size, although these are rare and the evolutionary history of genome size in amphibians has otherwise been one of gradual, time-dependent variation (that is, Brownian motion). This macroevolutionary homogeneity is remarkable given the evolutionary and ecological diversity of most other aspects of the natural history of amphibians. Contrary to previous claims, we find no evidence for associations between life cycle complexity and genome size despite the high diversity of reproductive modes and the multiple events of independent evolution of divergent life cycles in the group. Climate (temperature and humidity) affects genome size indirectly, at least in frogs, as a consequence of its effect on premetamorphic developmental period, although directionality of the relationship between developmental period and genome size is not unequivocal. Comparative quantitative analysis of factors shaping genome size evolution in amphibians reveals multiple (but rare) jumps in size against a background of gradual, time-dependent evolution.